Commercial real estate market in Belarus: concept, main types, specifications, forecast - Radenia, Aleksander M. (Journal of the Belarusian State University. Economics, 2021)
The article analyses the global trends of the commercial real estate market and gives its classification and monitors the growth dynamics of each segment of the Belarusian real estate market. Using trend and econometric models, a forecast of the Belarusian commercial real estate market up to 2025 was done.
Keywords: commercial real estate; real estate market trends; real estate investments; forecast models